Article 23(4) Trade Union Rights and the United Nations policy of devolution on labour relations. (3rd September 2019) - Hilgert, Jeffrey
ABSTRACT: Article 23(4) of the Universal Declaration of Human Rights states 'Everyone has the right to form and to join trade unions for the protection of his interests.' This article documents the global legislative history of Article 23(4) trade union rights from its original drafting to interpretation by international labour standards. The history includes debates on the fundamental principles of trade union rights, the decision by ECOSOC to ignore a call to establish a permanent UN Commission on Trade Union Rights, the devolution of authority from the United Nations to the International Labour Organization, how ILO international law experts framed trade union rights as a subset of the freedom of association, and the treatment of labour relations policy, including compulsory union membership, that resulted under international human rights norms. The history is discussed as one that confines standards of policy on labour rights in the global political economy and has particular implications for the discourse on labour rights as human rights.